Accuracy of Irradiance Forecasts Using JMA Numerical Weather Prediction Data at Numerous Points Corresponding to a High Degree of PV Penetration. Issue 2 (November 2015) - Nagoya, Hiroyuki; Saji, Kensuke; Aoki, Isao; Tanikawa, Ryoichi; Komami, Shintaro; Ogimoto, Kazuhiko; Iwafune, Yumiko
SUMMARY To assure power system stability when variable photovoltaic (PV) power generation is deployed on a large scale, accurate irradiance forecasting will be important in the near future. A substantial amount of PVs will be generating power at numerous locations in the power service area, and it will be necessary to predict the total PV output for supply/demand balancing control. Therefore, irradiance forecasting accuracy should be verified using the total irradiance at numbers of sites equivalent to areas with large‐scale PV deployment. This paper reports an investigation of the accuracy of an approach to area total irradiance prediction based on regional numerical weather prediction data from the Japan Meteorological Agency. The forecast area total irradiance is compared to the assumed total area irradiance for numbers of sites equivalent to large‐scale PV deployment.